Outcome for Advanced or Metastatic Soft Tissue Sarcoma of Nonextremities Treated with Doxorubicin-Based Chemotherapy: A Retrospective Study from a Single Cancer Institution. (18th April 2018) - Marshall, Shoko; Nakano, Kenji; Sugiura, Yoshiya; Taira, Shinichiro; Ono, Makiko; Tomomatsu, Junichi; Takahashi, Shunji
Abstract : Background . Doxorubicin is the key drug for treatment of advanced soft tissue sarcoma (STS). The appropriate dosage of doxorubicin, regarding monotherapy or the role of combination therapy, is unclear. Methods . We retrospectively reviewed patients with advanced or metastatic STS of nonextremities who were treated with doxorubicin-based chemotherapies in our institution. Time to treatment failure (TTF), overall survival (OS), overall response, and prognostic factors for OS were evaluated. Results . Seventy-five patients were enrolled. The median TTF was 4.7 months, and the median OS was 20.1 months. The overall response rate was 20%. Doses of doxorubicin monotherapy did not show significant difference either in TTF or in OS. There were no significant differences in OS between combination therapy and monotherapy, but the TTF with combination therapy was better than monotherapy. The overall response for combination therapy indicated a better response rate. Less number of involved organs, no bulky mass, and a normal CRP level were independent favorable prognostic factors for OS. Conclusions . Combination therapy showed better response and TTF than monotherapy but did not show better OS. Possible prognostic factors for OS were indicated. This retrospective study was approved by the institutional review board. This trial is registered withUMIN000028787 .